# [SOLVED] Algebra homework - please check if these are right -&gt;

• Aug 13th 2008, 05:25 AM
Neenoon
[SOLVED] Algebra homework - please check if these are right -&gt;
I'm working on my second homework, as I've mentionned before this is a math class I'm taking to get myself up to college math. I'm starting my master's in Human Ress, but I haven't done math since high school, about 20 years ago. My brain just doesn't work as good as it used too? (Thinking)

If someone would just check if those 3 answers are correct, that would be of great help.

If:
P1= 12x^2-6xy+9y^2
P2= -2x^2+3xy-4y^2
P3= 2x-y^2

And:
M1= -3xy

1) P3-P2

=(2x-y^2)-(-2x^2+3xy-4y^2)
=(2x-y^2)+(2x^2-3xy+4y^2)
=2x+(-y^2+4y^2)+2x^2-3xy
=2x+3y^2+2x^2-3xy

2) P2XP3

=(-2x^2+3xy-4y^2) (2x-y^2)
=(-2x^2)x2x+(-2x^2)x(-y^2)+3xyx2x+3xyx(-y^2)+(-4y^2)x2x+(-4y^2)x(-y^2)
=(-4x^3)+2x^2y^2+6x^2y-3xy^3-8xy^2+4y^4

3)P1/M1

=12x^2-6xy+9y^2
----------------
-3xy
=12x^2 -6xy 9y^2
------ + ----- + ------
-3xy -3xy -3xy

=-4xy^-2+0.5+-3x^-1y
=-4xy^-2-x^-1y+0.5
=-7x^-1y^-1+0.5
=0.5
----
7xy

Those are the first three, I'm trying my best not to check everything with you guys because the homework is extensive and I've already had to ask for a prolongation, which cost me 60$more (on top of the 350$+ they charged for the class), so believe me when I say that this is important for me and you guys are not wasting your time helping me out.

Thank you so much

Neenoon
• Aug 13th 2008, 06:01 AM
Chop Suey
First two are correct. I'm not sure what you wrote in the last one, but here it is anyways:

$\displaystyle \frac{12x^2 - 6xy + 9y^2}{-3xy}$

$\displaystyle = \frac{-12x^2 + 6xy - 9y^2}{3xy}$

$\displaystyle = \frac{-12x^2}{3xy} + \frac{6xy}{3xy} - \frac{9y^2}{3xy}$

$\displaystyle = -\frac{4x}{y} + 2 - \frac{3y}{x}$

$\displaystyle = -4xy^{-1} + 2 - 3yx^{-1}$

P.S. You brain works just as good as before, if not better. :D (Yes)
• Aug 13th 2008, 06:08 AM
Simplicity
Quote:

Originally Posted by Neenoon

If:
P1= 12x^2-6xy+9y^2
P2= -2x^2+3xy-4y^2
P3= 2x-y^2

And:
M1= -3xy

1) P3-P2

=(2x-y^2)-(-2x^2+3xy-4y^2)
=(2x-y^2)+(2x^2-3xy+4y^2)
=2x+(-y^2+4y^2)+2x^2-3xy
=2x+3y^2+2x^2-3xy

This is correct.

Quote:

Originally Posted by Neenoon
2) P2XP3

=(-2x^2+3xy-4y^2) (2x-y^2)
=(-2x^2)x2x+(-2x^2)x(-y^2)+3xyx2x+3xyx(-y^2)+(-4y^2)x2x+(-4y^2)x(-y^2)
=(-4x^3)+2x^2y^2+6x^2y-3xy^3-8xy^2+4y^4

This is correct too.

Quote:

Originally Posted by Neenoon
3)P1/M1

=12x^2-6xy+9y^2
----------------
-3xy
=12x^2 -6xy 9y^2
------ + ----- + ------
-3xy -3xy -3xy

=-4xy^-2+0.5+-3x^-1y
=-4xy^-2-x^-1y+0.5
=-7x^-1y^-1+0.5
=0.5
----
7xy

Here I got:

$\displaystyle -4xy^{-1} + 2 -3x^{-1}y$
• Aug 14th 2008, 01:51 PM
Neenoon
Thank you so much, I was a bit off on that last one. I think I get it now (oh, and I'll trying doing whatever you are doing to post the equation so that they are more readable).